The Addition of α-Hydroxy-benzylphosphonates to Dialkyl Acetylenedicarboxylates; Catalytic Hydrogenation of the Adducts - Milen, Mátyás; Bese, Cintia; Kovács, Csenge; Dancsó, András; Keglevich, György (Synthesis, 2024)
α-Hydroxy-benzylphosphonates obtained by the Pudovik reaction of substituted benzaldehydes and dialkyl phosphites were added to the triple bond of dialkyl acetylenedicarboxylates. Optimum conditions involved a 24 hours stirring in the presence of 10% diazabicycloundecene in dichloromethane to afford the adducts as a mixture of predominant E- and a minor Z-isomers in 75–90% yields after flash chromatography. The structures of the geometrical isomers were confirmed by NOE- and ROE-measurements. Catalytic hydrogenation of the olefinic moiety of the adducts led to the diastereoisomers of corresponding saturated derivatives.
Keywords: addition; alkenation; alkylation; hydrogenation; phosphates